Analisis Biochemical Oksigen Demand (BOD) pada Sampel Air Sungai Konsumen Menggunakan Metode Winkler di UPTD Laboratorium Lingkungan Kota Pariaman - Mutiara Dea Ananda; Miftahul Khair (Lembaga Yasin AlSys, 2026)
Biochemical Oxygen Demand (BOD) is an important parameter in water quality assessment because it indicates the amount of dissolved oxygen required by microorganisms to biologically degrade organic compounds. This study aims to analyze BOD values in river water samples in Pariaman City as an indicator of the level of organic pollution in aquatic environments. Testing was conducted using the BOD method by measuring dissolved oxygen (DO) levels on day 0 and day 5 after incubation at 20 ± 1 °C. The analyzed samples consisted of three sample codes, namely S.186, S.187, and S.188. The test results showed that all samples experienced a decrease in DO levels after five days of incubation. The BOD values obtained were 2.84 mg/L in sample S.186, 1.95 mg/L in sample S.187, and 3.28 mg/L in sample S.188, respectively. The highest BOD value was found in sample S.188, indicating a higher organic matter content than the other samples. The quality control results showed that the blank, mineral-free water, glucose-glutamate standard, and percentage Relative Percent Difference (%RPD) met the method requirements, so the test data were declared valid. The conclusion of the study shows that the water quality of the analyzed samples was in the low to moderate pollution category. These findings have implications as supporting data in the evaluation of river water quality through environmental laboratory testing and as a basis for periodic water quality monitoring.